A comparison of two scales for assessing health professional students’ attitude toward interprofessional learning - Désirée Annabel Lie; Cha Chi Fung; Janet Trial; Kevin Lohenry (Medical Education Online, 2013)
Rationale : The validated 19-item Readiness for Interprofessional Learning Scale (RIPLS) is often used for assessing attitudes toward interprofessional education (IPE). The 12-item Interdisciplinary Education Perception Scale (IEPS), also used for this purpose, has not been validated among the professions of medicine, pharmacy, and physician assistants (PAs). The discriminatory ability of the two scales has not been directly compared. Comparison of the two will aid educators in selecting the optimal scale. Objective : To compare psychometric properties of the RIPLS and IEPS and to examine the ability of each scale to discriminate mean scores among student subgroups (gender, profession, seniority, and prior IPE exposure). Method : We conducted a cross-sectional (Qualtrics©) survey (RIPLS and IEPS) of junior and senior students in medicine (n=360), pharmacy (n=360), and the PA profession (n=106). Descriptive statistics were used to report aggregate mean scores of subgroups. The internal consistency of each scale was assessed using Cronbach's α. Concurrent validity was measured by Pearson's correlation coefficients. Independent-sample t-tests and analysis of variances (ANOVAs) were performed to assess the discriminatory ability of each scale. Cohen's d effect sizes were calculated for all significant pair-wise comparisons. Results : Response rate was 82%. Cronbach's α was 0.85 (RIPLS) and 0.91 (IEPS). The RIPLS discriminated scores by gender among junior students only, and scores by IPE exposure among all students. The IEPS distinguished score differences for the three professions among junior students and by prior IPE exposure for all three professions. Neither scale detected differences in mean scores by profession among all students or by level of training among the three professions. Conclusions : Neither the RIPLS nor the IEPS has greater discriminatory ability for detecting attitude differences among the student subgroups. Reason for differences may be explained by slightly different scale constructs. The RIPLS is designed to assess students’ own attitude toward interprofessional learning, while the IEPS discerns perceived attitudes about team collaboration for students’ own professions and may be more appropriate for more advanced students.